The Effect of the Teams Games Tournament (TGT) Learning Model on Students’ Learning Activities and Learning Outcomes in the Topic of Viruses among Tenth-Grade Senior High School Students - Jessica Sonia Pasaribu; Martina Asiati Napitupulu (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to determine the effect of the Teams Games Tournament (TGT) learning model on students’ learning activities and learning outcomes in the topic of viruses among Grade X senior high school students. The study employed a quasi-experimental method using a Non-Equivalent Control Group Design. The sample was selected through purposive sampling based on the equivalence of pretest scores, resulting in Class X-3 as the experimental group and Class X-4 as the control group, with 34 students in each class. The research instruments consisted of multiple-choice questions to measure learning outcomes and observation sheets to assess students’ learning activities. The data were analyzed using parametric statistics, including tests of normality, homogeneity, and a one-tailed independent-samples t-test (right-tailed). The results showed that the mean score of students’ learning activities in the experimental class (79.67) was higher than that in the control class (44.31), with a significance value of 0.000 < 0.05. Similarly, the mean learning outcome score in the experimental class (84.71) was higher than that in the control class (79.56), with a significance value of 0.0045 < 0.05. Therefore, the TGT learning model was effective in improving both students’ learning activities and learning outcomes in the topic of viruses for Grade X senior high school students and may serve as an alternative interactive biology teaching strategy to help students understand the abstract concept of viruses.